HIRSCHSPRUNG'S DISEASE- DIAGNOSIS, TREATMENT AND NEW THERAPEUTIC STRATEGIES - Agnieszka Bajkacz; Izabela Polakowska; Wiktoria Marzec (International Journal of Innovative Technologies in Social Science, 2026)
Hirschsprung's disease (HD, HSCR) is a congenital disorder of intestinal motility characterized by aganglionosis. It is the absence of ganglion cells in the nerve plexuses of the large intestine. It leads to peristalsis disorders and functional obstruction. The disease most often manifests itself in the neonatal period as delayed meconium passage, abdominal distension, vomiting, and symptoms of obstruction. Confirmation of the diagnosis requires a rectal biopsy with histopathological evaluation. Treatment consists of surgical removal of the aganglionic segment of the intestine and restoration of the continuity of the gastrointestinal tract. The choice of surgical method depends mainly on the surgeon's preference and the experience of the center. A common complication is Hirschsprung-associated enterocolitis (HAEC), which may occur before or after surgery. Research is currently underway on the use of cell therapy in the treatment of HD. The review presents the epidemiology, pathogenesis, diagnosis, and current therapeutic strategies for Hirschsprung's disease, with particular emphasis on recent reports from the scientific literature. We highlight also new directions in research and therapeutic perspectives.Aim of this study: The objective of this study is to summarise the latest information on Hirschsprung's disease, including research on cell therapies and treatments aimed at tissue regeneration.Materials and methods: A literature review was conducted using the professional PubMed database. Articles published between 2018 and 2025 were included. The searches included combinations of the keywords: “Hirschsprung's disease,” “pediatric surgery,” “aganglionosis,” and “stem cell therapy”.